Post‐exposure prophylaxis in the era of pre‐exposure prophylaxis. Issue 10 (9th September 2020) - Atim, M; Girometti, N; Hyndman, I; McOwan, A; Whitlock, G; ,
Abstract : Objectives: 56 Dean Street (56DS), a sexual health clinic in London, provides a quarter of England's HIV post‐exposure prophylaxis following sexual exposure (PEPSE). Since the limited introduction of pre‐exposure prophylaxis (PrEP) in 2015, PEPSE demand has fallen. Methods: We performed a case‐note review of individuals who received PEPSE at 56DS in August 2018. Results: Two hundred and forty three PEPSE were given; 97% (236) fitted recommended indications according to UK national guidance. Twenty‐eight (12%) had documented prior PrEP use; the most common reason for not taking PrEP was lack of supply (15/28; 54%). Up to 1st April 2020, of 215 who had not previously used PrEP, 106 (49%) re‐attended 56DS for PrEP initiation. Conclusions: At 56DS, PEPSE is appropriately given for high‐risk HIV exposures. For those who use PrEP, It is important to support their adherence and ensure adequate supply. As PrEP uptake increases, the need for PEPSE may decrease.